2004
DOI: 10.1158/1078-0432.ccr-04-0561
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Nuclear Receptor Coactivator AIB1 ( SRC-3 ) during Progression of Pancreatic Adenocarcinoma

Abstract: Purpose: The nuclear receptor coactivator amplified in breast cancer 1 (AIB1) was found to be amplified and overexpressed in breast and some other epithelial tumors. We have reported that expression of AIB1 is rate limiting for growth factor, as well as hormone signaling. Here, we assess the involvement of AIB1 in the development of pancreatic adenocarcinoma.Experimental Design: We investigated expression levels of AIB1 protein and mRNA in pancreatic cancer cell lines and in a series of archival pancreatic ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(83 citation statements)
references
References 34 publications
6
74
0
2
Order By: Relevance
“…Genetic ablation of AIB1 inhibits spontaneous prostate cancer progression in mice (Chung et al, 2007), indicating that AIB1 has a role in promotion of prostate cancer progression. Several other studies showed that AIB1 is overexpressed in human colon, pancreas and stomach cancers and may contribute to the development of metastases (Sakakura et al, 2000;Henke et al, 2004;Xie et al, 2005). These results indicate that AIB1 is a bona fide oncogene.…”
Section: Introductionmentioning
confidence: 64%
“…Genetic ablation of AIB1 inhibits spontaneous prostate cancer progression in mice (Chung et al, 2007), indicating that AIB1 has a role in promotion of prostate cancer progression. Several other studies showed that AIB1 is overexpressed in human colon, pancreas and stomach cancers and may contribute to the development of metastases (Sakakura et al, 2000;Henke et al, 2004;Xie et al, 2005). These results indicate that AIB1 is a bona fide oncogene.…”
Section: Introductionmentioning
confidence: 64%
“…Given that we have found that the expression of AIB1-⌬4 at the protein level is higher in breast and pancreatic cancer cells (17,61), we were interested to investigate if AIB1-⌬4 is regulated at the protein level. We have previously shown that AIB1 protein levels are greatly reduced in response to growth of cells at high confluence and the removal of growth factors (62).…”
Section: Discussionmentioning
confidence: 99%
“…In both Western blotting and immunocytochemical analysis, the SRC-1 antibody was used at 1:200, and the TIF2 and TRAM-1 antibodies were used at 1:150. These antibodies have previously been used successfully for immunohistochemistry and/or Western-blot analysis (23,26,27).…”
Section: Antibodiesmentioning
confidence: 99%
“…The monoclonal antibodies for three coactivators used in the present study were previously characterized to serve as valid probes (23,26,27,32). In fact, the Western blotting of cellular extracts from rat testis using each antibody detected a major 160 kDa band (Fig.…”
Section: Specificity Of Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation